The Effect of Compensation, Employee Well-Being and Work Motivation on the Performance of Employees of Sharia Savings and Loan Cooperatives : (Case Study of BMT NU East Java, Situbondo Regency) - Moh Irfan Affandi; Purnamie Titisari; Diana Sulianti K. Tobing (Harmony Management: International Journal of Management Science and Business, 2025)
The purpose of this study is to determine the effect of compensation, employee well-being and work motivation as intervening variables on employee performance, this study will test the direct and indirect effects. In this study using quantitative research methods. The number of samples used in this study totalled 112 respondents. By using saturated sampling technique where the entire population is sampled. By using Smart PLS version 3, the analysis results show that 1) compensation has a significant effect on employee well being 2) compensation has a significant effect on work motivation 3) compensation has a significant effect on employee performance 4) employee well being has a significant effect on employee performance 5) work motivation has a significant effect on employee performance 6) compensation mediates the effect of employee well being on employee performance 7) compensation mediates the effect of work motivation on employee performance.